The Implementation of Visual Communication Design for the Visual Identity of Lihai Islamic Preschool Bandung - Hidayat, Syarip; Kusuma Ayu, Intan (Universitas Negeri Semarang, 2024)
Preschool education in Indonesia, particularly in the vibrant city of Bandung, plays an important role in laying the foundation for a child's overall development. As the country strives to preserve its diverse cultural and religious heritage, there is a growing emphasis on integrating Islamic religious education into early childhood learning environments. Bandung with its diverse population has provided education to instill religious values from an early age. Preschool education in Bandung needs a design to convey information about Islamic religious education with a nature approach that emphasizes care for the environment and appreciation of the rich diversity of nature. Visual communication design can provide this solution for preschool institutions to create a unique identity that reflects local culture and values. This approach not only gives children a strong grounding in Islamic teachings and environmental awareness, but also fosters a deep connection with nature from a young age, other programs aligned with this are activities such as gardening, nature walks, and environmental learning in an Islamic perspective, preschools in Bandung can be needed to develop a unique identity that reflects local culture and the natural surroundings. The above conditions have described the needs that need to be implemented in visual solutions that can help to inform the program that has been described through a community service program with this appropriate art application scheme, in this case the target partner is Lihai Islamic Preschool, this institution was chosen as a target partner due to the suitability of the program being run and in accordance with the community service program to be implemented. Lihai Islamic Preschool is located at Jalan lembah Cisitu No. 5 Dago Bandung 40135.